Price Volatility of Horticulture Commodity During the Pandemic in East Java, Indonesia - Hartono, Rachman; Rahman, Moh. Shadiqur; Retnoningsih, Dwi; Shaleh, Mohammad Ilyas (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2023)
In the past two years, market information and the distribution of agricultural products have been affected by the COVID-19 pandemic, which has limited the distribution of information and the movement of agricultural products. As a result, the COVID-19 pandemic can lead to non-competitive behavior among intermediary traders, especially those operating in concentrated markets. This research aims to analyze the price volatility of horticulture commodity during the pandemic in East Java, Indonesia. The research data was collected through the official website of the Information System for Availability and Price Development of Basic Necessities in East Java (SISKAPERBAPO). The method used to analyze the impact of COVID-19 on horticultural agricultural product prices is ARCH (Autoregressive Conditional Heteroscedastic) and GARCH (Generalized Autoregressive Conditional Heteroscedasticity). The volatility results show that the prices of chili and shallots often fluctuate with high and unpredictable variations. However, the fluctuations in the prices of these two commodities are not due to a lack of supply or high demand, but rather due to the characteristics of these commodities, which are perishable and highly dependent on the season of production. The lower the quality, the lower the price will be. The price of shallots is relatively stable compared to chili due to its longer shelf life and less depreciation. The constraint faced by farmers of these two commodities during harvest time is the lack of storage facilities to store their harvest, forcing them to sell all their produce to middlemen or traders, which is one of the causes of the fluctuation of commodity prices.